Alkene–Azide 1, 3‐Dipolar Cycloaddition as a Trigger for Ultrashort Peptide Hydrogel Dissolution. Issue 8 (13th November 2018) - Dadhwal, Sumit; Fairhall, Jessica M.; Goswami, Shailesh K.; Hook, Sarah; Gamble, Allan B.
Abstract: An alkene–azide 1, 3‐dipolar cycloaddition between trans ‐cyclooctene (TCO) and an azide‐capped hydrogel that promotes rapid gel dissolution is reported. Using an ultrashort aryl azide‐capped peptide hydrogel (PhePhe), we have demonstrated proof‐of‐concept where upon reaction with TCO, the hydrogel undergoes a gel–sol transition via 1, 2, 3‐triazoline degradation and 1, 6‐self‐immolation of the generated aniline. The potential application of this as a general trigger in sustained drug delivery is demonstrated through release of encapsulated cargo (doxorubicin). Administration of TCO resulted in 87 % of the cargo being released in 10 h, compared to 13–14 % in the control gels. This is the first example of a potential bioorthogonal‐triggered hydrogel dissolution using a traditional click‐type reaction. This type of stimulus could be extended to other aryl azide‐capped hydrogels. Abstract : Click‐to‐dissolve : An alkene–azide click‐reaction is used to promote hydrogel dissolution. The stable gel can encapsulate a cargo (e.g., doxorubicin) and upon addition of the strained alkene (a trans ‐cyclooctene), the click‐reaction leads to gel dissolution and release of the encapsulated cargo.